Are opioid antagonists effective in reducing self‐injury in adults with intellectual disability? A systematic review. (7th January 2014) - Roy, A.; Roy, M.; Deb, S.; Unwin, G.; Roy, A.
Abstract Background Self‐injury in people with intellectual disability (ID) may be due to variety of factors both environmental and biological. As the drive in UK is to manage people with ID and problem behaviours in the community, it is important to critically examine all treatment options available. As abnormalities in the endogenous opioid system may be a factor in some people with ID, we undertook a systematic review to evaluate the evidence for the effectiveness of opioid antagonists. Methods Four electronic databases were searched for relevant journal articles. In addition, cross‐referencing of pertinent reviews and a hand search for articles in major international ID journals between the years 2010 and 2012 was carried out to ensure that all relevant articles were identified. We also searched databases for unpublished clinical trials to overcome publication bias. Each database was searched up to present (February 2013) with no restrictions on the date of publication. The search terms consisted of broad expressions used to describe ID and autistic spectrum disorder as well as terms relating to opioid antagonists and specific drugs. All studies identified by the electronic database search and hand search were examined on the basis of title alone for relevance and duplication. The abstracts of the remaining papers were then scrutinised against the inclusion criteria. Where abstracts failed to provide adequate information, the full texts for these papers were obtained. All the full texts were then evaluated against the inclusion proforma. Two reviewers carried out all the stages of the process independently. The reviewers met to discuss their selections and where disagreements arose, these were settled by discussion with a member of the study group. Data from each study meeting the inclusion criteria was extracted on a pre‐piloted data extraction form. The quality of each study was further assessed using the Jadad scale, a tool developed to assess the quality of randomised controlled trials. Results Out of 10 randomised control trials eight reported a reduction in the frequency of self‐injurious behaviour. This meant that 62 participants out of 124 (50%) showed an improvement of which 61 were statistically significant. Forty‐nine participants had autism. Eleven (9%) had minor side‐effects. The improvement was more marked in people with severe and profound ID and was not affected by the coexistence of autism. Conclusions This review suggests that some people respond to opioid antagonists with a reduction in self‐injury but the trials do not predict who they may be. Future research may identify this sub‐group when opioid antagonists may prove to be a useful addition in the pharmacotherapy of self‐injury.